Job Satisfaction of Public and Private Healthcare Centers in Rangpur City Corporation Area: A Comparative Study - Isrot, Afifa (Asian Business Review, 2022)
This study compares public and private hospital employees' job satisfaction. The study's objective is a comparative analysis of employee job satisfaction in public and private healthcare centers concerning employee management systems and motivational factors. Respondents have been selected from the public and private healthcare centers of Rangpur City Corporation.   The study observed that the views of public and private healthcare employees are volatile in many ways. It's also observed that private hospitals follow systematically and scientifically EMM practices, creating high employee satisfaction levels. In addition, public healthcare workers are more satisfied with the terms and conditions of their workplace than private health workers.